Solidaritas dan Ketahanan Psikologis: Peran Sense of community dan Durasi Keanggotaan Komunitas terhadap Resiliensi pada Pengendara Ojek Online - Wibowo, Dwi Prasetyo; Bagaskara, Sunu; Putra, Johan Satria (Universitas Trunojoyo Madura, 2025)
The pandemic imposed significant economic and psychological stress, particularly on informal workers such as online drivers. This study aims to explore the role of sense of community and membership tenure with resilience on online ride-hailing (ojek) drivers in Jakarta during the COVID-19 pandemic. Data were collected from 100 participants meeting inclusion criteria through a survey using two primary instruments: the Connor-Davidson Resilience Scale (CD-RISC) to measure resilience and the Psychological Sense of community Scale (PSCS) to assess sense of community. Multiple linear regression analysis revealed that sense of community significantly contributed to resilience (β = 1.746; p 0.001), whereas community membership duration showed no significant relationship (β = 0.127; p = 0.795). These findings suggest that the quality of psychological attachment within the community plays a greater role in enhancing resilience than the length of membership. This research highlights the importance of community-based psychological support as a buffer against stress during crises. Beyond providing new insights in the pandemic context, the findings are practically relevant for developing community-based strategies to improve the psychological resilience and well-being of online ride-hailing drivers as a vulnerable group.